Advancing Farmer-Led Low-Emission Small Ruminants Production: Partners, Beneficiaries & Climate-Smart Innovations in Ethiopia and Beyond - Getachew, Tesfaye; Rischkowsky, Barbara A.; Belay, Berhanu; Rekik, Mourad; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Since its inception in Ethiopia in 2009, the Community-Based Breeding Program (CBBP) which led by ICARDA and national partners, has grown from a pilot in six villages into a globally recognized model for sustainable small-ruminant genetic improvement. By 2025, the program covered 268 CBBP and Production Unit villages (252 in Ethiopia and 16 in the five partner countries), directly engaging 95,700 smallholder households and managing 198,993 animals in Ethiopia. Through the SmaRT Pack innovation framework, the program integrates eight complementary innovations, genetic improvement, low-cost Artificial Insemination (AI), ultrasonography for reproductive management, feed development and utilization, digital data systems (DTREO), market linkage models, inclusive youth and women engagement, improved husbandry practices, and enhanced animal-health interventions. Together, these have transformed traditional breeding systems into climate-smart, market-linked platforms. In 2025, capacity development remained central to scaling CBBPs and Smart Pack innovations. Three national ToTs organized by MoA, ICARDA, the CGIAR Sustainable Animal and Aquatic Food (SAAF) initiative and AICCRA trained 86 senior experts (11 women), who subsequently cascaded knowledge through over 90 field trainings reaching 2,200 participants (38% women), including cooperative leaders, enumerators, development agents, and key farmers. AICCRA played a pivotal role by supporting digital data systems, climate-smart breeding indices, and the establishment of Production and Finisher Units linking improved genetics to markets. Implementation now engages over 90 institutional partners, including 14 research centers, 23 universities, the Ethiopian Biodiversity Institute (EBI), the Ministry of Agriculture (MoA), the Livestock Development Institute (LDI), nine Regional Bureaus of Agriculture (BoAs), and more than 40 district livestock offices. The program is supported by national and international donors, notably AICCRA, the World Bank (LLRP, LFSDP) and ACIAR, CGIAR initiatives. The CBBP framework, now a core component of Ethiopia’s national small-ruminant genetic improvement and red-meat strategy, has achieved measurable outcomes, 20% average income growth, 68% increase in carcass yield per breeding flock, and about 28% reduction in emission intensity (kg CO₂-eq/kg carcass), showing that farmer-led breeding systems can simultaneously enhance productivity and climate resilience. Anchored in Ethiopia and expanded through ICARDA’s global partnerships and AICCRA-supported scaling, this network stands among the world’s largest farmer- led livestock genetic improvement initiatives, driving productivity, climate resilience, and inclusive livestock transformation across Africa and Asia. Building on AICCRA’s investments in digital and climate-smart pathways, future priorities will deepen SmartPack adoption, expand genetic dissemination, and integrate genomic, reproductive, and GHG emission measurement innovations within breeding programs to further strengthen institutional capacity, sustainability, and climate accountability